Electrochemical Synthesis and Electro-Optical Properties of Dibenzothiophene/Thiophene Conjugated Polymers With Stepwise Enhanced Conjugation Lengths - Lin, Kaiwen; Li, Caiting; Tao, Wang; Huang, Jilong; Wu, Qinghua; Liu, Zijin; Zhang, Yangfan; Wang, Da; Liu, Xi (Frontiers in Chemistry, 2020)
A total of six conjugated polymers, namely PDBT-Th, PDBT-Th:Th, PDBT-2Th, PDBT-Th:2Th, PDBT-2Th:Th, and PDBT-2Th:2Th, consisting of dibenzothiophene, thiophene, and bithiophene were electrochemically synthesized. Their electrochemical and electrochromic properties were investigated in relation to the conjugation chain lengths of the thiophene units in the conjugated backbones. Density functional theory (DFT) calculations showed that longer conjugation lengths resulted in decreased HOMO-LUMO gaps in the polymers. The optical band gaps (Eg,opt) and electrochemical band gaps (Eg,cv) were decreased from PDBT-Th to PDBT-Th:Th, however, PDBT-Th:2Th, PDBT-2Th, PDBT-2Th:Th and PDBT-2Th:2Th displayed the similar band gaps. The conjugation length increments significantly improved the electrochemical stability of the conjugated polymers and exhibited reversible color changes due to the formation of polarons and bipolarons. The results suggest that the conjugated polymers prepared herein are promising candidates for fabricating flexible organic electrochromic devices.